GENDER-FRIENDLY PROGRESSIVE INTERPRETATION: THE CONCEPT OF ANGELS IN THE QUR'AN WITH THE PARADIGM OF QIRĀAH MUBĀDALAH - Gandhung Fajar, Panjalu; Muhammad Arfan, Muammar; Abdul, Mujib (Musawa: Journal for Gender Studies, 2025)
This research employs the Qira′ ah Mubādalah approach to offer a progressive and gender-sensitive interpretation of the concept of the bidadari (houris) in the Qur'an, particularly for verses often interpreted with a gender-bias and anthropocentric perspective (QS. Al-Waqi'ah: 22-23, QS. Ad-Dukhan: 54, and QS. Ar-Rahman: 72). Using a qualitative method and thematic analysis (maudhu′i), the study found that conventional interpretations have reduced the spiritual meaning into the physical objectification of women. Through the Qira′ah Mubādalah principles of reciprocity and substantive equality, the concept of the bidadari is reconstructed as a symbol of the ideal heavenly spouse (azwaj mutahharah) promised equally to all believers both men and women, thereby ensuring eschatological justice. Female believers are guaranteed the right, equivalent to men, to receive a sanctified partner who mutually honors them. For those who were unmarried, widowed/divorced, or for women who experienced polygamy in this world, Paradise promises the perfection of exclusive and equal relationships tailored to their spiritual rank, ultimately transforming the understanding of the huri into a vision of spiritual justice.